A Gambaran Kadar Asam Urat pada Pasien Hemodialisis rutin di RSUD Provinsi NTB: Gambaran Kadar Asam Urat pada Pasien Hemodialisis rutin di RSUD Provinsi NTB - Ni Komang Miraditi Miraditi; I Gede Yasa Asmara; Raehanul Bahraen (Lombok Medical Journal, 2024)
According to the United States Renal Data System, there were 124,411 patients with end-stage renal disease (ESRD) in 2015, and the number is estimated to increase by 20,000 cases per year. The decline in kidney function in ESRD patients leads to various clinical conditions, one of which is an increase in blood uric acid levels. Studies on patients who have not undergone hemodialysis (HD) found that 86.7% of patients experienced hyperuricemia, compared to 73.3% of patients who had already undergone HD. This study aims to describe the uric acid levels in ESRD patients undergoing HD at the NTB Provincial Hospital. This research used an analytical observational method with a cross-sectional study design based on secondary data (medical records) of ESRD patients undergoing HD at the NTB Provincial Hospital from January to August 2021. The sampling technique used was consecutive sampling. The data obtained were then analyzed using the Statistical Package for Social Sciences (SPSS). Among the 127 samples, the average uric acid level in HD patients was found to be 8.0 mg/dl, with 83 patients (65.4%) having hyperuricemia. More male patients (43 or 51.8%) had hyperuricemia compared to female patients (40 or 48.2%), and the highest incidence of hyperuricemia was found in patients aged 40-59 years, accounting for 67.5%. Bivariate chi-square analysis showed no significant association between uric acid levels and gender (p=0,590), age (p=0,152), duration of HD (p=0,730), or history of anti hyperuricemic treatment (p=0,613). This study concludes that the incidence of hyperuricemia in HD patients is high. Uric acid levels are not associated with age, gender, duration of hemodialysis, or history of anti-hyperuricemic treatment.